COVID-19 Pandemic and Road Ahead - Hiremath, Shobha Rani R (Indian Journal of Pharmacy Practice)
It is evident that COVID-19 cases are raising constantly in the country and worldwide. As on October 30, 2020, there were over 45 million global cases of COVID-19. Over 33 million people had recovered from the disease and the recovery rate is found to be quite satisfactory, while there had been over 1.1 million deaths.